2011
DOI: 10.1007/s11524-011-9570-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Networks and Housing Stability

Abstract: Unstable housing is related to a range of health problems including substance abuse, poor mental health, and HIV. Little is known about how sexual partners' attributes influence access to resources such as housing. The purpose of the present study was to examine the relationship between sexual network characteristics and improvements in housing situation among a sample of drug users using a longitudinal design. Size of one's sex network was not associated with housing change. However, having a main partner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This suggests that some of the unadjusted association between individual-level variables such as homelessness and exchange sex may be explained by distal factors (i.e., perceived neighborhood disorder and social network variables). This is in agreement with an explanation proposed by Sterk and colleagues, which suggests that individuals who have lower social capital and/or live in neighborhoods with greater disorder may be more susceptible to poor health-related conditions, such as homelessness [39, 57]. …”
Section: Discussionsupporting
confidence: 92%
“…This suggests that some of the unadjusted association between individual-level variables such as homelessness and exchange sex may be explained by distal factors (i.e., perceived neighborhood disorder and social network variables). This is in agreement with an explanation proposed by Sterk and colleagues, which suggests that individuals who have lower social capital and/or live in neighborhoods with greater disorder may be more susceptible to poor health-related conditions, such as homelessness [39, 57]. …”
Section: Discussionsupporting
confidence: 92%
“…Also, the lack of a direct association between homeless severity and unprotected sex suggests that the immediate condition of homelessness is the dominant factor shaping relationship outcomes. Other studies have also identified homelessness as a dominant factor in shaping the quality of sexual relationships [56]. Homelessness is often the main context in which risk factors for HIV risk take place for homeless people [19] and there have been arguments that housing assistance to those who are homeless or precariously housed offers the best and most direct form of HIV prevention [88].…”
Section: Discussionmentioning
confidence: 99%
“…AOD use is both a leading cause of homelessness [ 5 ] and is exacerbated by the stress of life on the street and exposure to high rates of AOD use among other homeless people [ 6 8 ]. Exposure to HIV is a significant health threat for homeless individuals, with rates of HIV infection being three to nine times greater among homeless persons than those with stable housing [ 4 , 9 , 10 ]. The greater vulnerability to HIV among homeless individuals is due, in part, to AOD use increasing their likelihood of engaging in risky sexual behaviors such as having unprotected sex and trading sex.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks have the potential to influence health behaviors and outcomes through social comparison, social sanctions and rewards, information transmission, support and resources, stress reduction, and socialization [ 24 29 ]. A large and growing body of research demonstrates both the positive and negative influences of social network on the lives of homeless individuals [ 30 32 ], including their health and health-related behaviors [ 7 , 9 , 33 , 34 ]. For example, social networks are an important source of social support and thus may influence (positively or negatively) AOD use, HIV risk behavior, AOD treatment program participation, and successful transition out of homelessness [ 6 8 , 17 , 33 39 ].…”
Section: Introductionmentioning
confidence: 99%